Children-at-Risk and the Whole Gospel: Integral Mission 'To, For, and With' Vulnerable Agents of God. (July 2016) - Greener, Susan Hayes
The author encourages the Church to conceptualize children-at-risk as whole, complex humans, who actively participate in their own development and experience multi-directional influences within the contexts of families, communities, cultures, and histories. This view of children requires an expanded understanding of the whole gospel moving past children-at-risk as subjects of evangelism and advocacy. Children are seen as vulnerable agents of God, participants in their own development, and co-participants with the Church in the missio Dei . Using a hermeneutic of inclusion, a model of integral mission 'to, for, and with' children-at-risk is offered.